Market concentration and business survival in static v dynamic industries - Andrew E. Burke; Aoife Hanley (Kiel Institute for the World Economy (IfW), 2009)
We propose that the effect of market concentration on firm survival is different according to whether an industry is static (low entry and exit) or dynamic. In our empirical analysis we find support for this hypothesis. Industry concentration rates reduce the survival of new plants but only in markets marked by low entry and exit rates. Specifically, a 10 percent increase in the 5-firm concentration ratio in a dynamic market raises the survival rate of new ventures by approximately 2 percent. Our results have implications for the antitrust/competition law indicating less need for regulation of dominant firms in dynamic industries characterized by high entry and exit rates. We use a unique dataset comprising the population of new ventures that enter the UK market in 1998.
Keywords: L11; L25; M13; M40; 330; New firms; start-ups; survival; dynamism; competition policy; industry concentration; Wirtschaftskonzentration; Markteintritt; Unternehmensgründung; Unternehmensentwicklung; Industrieökonomik; Wettbewerbspolitik; Großbritannien